Analisis Perbandingan Perhitungan PPh Pasal 21 Penggunaan Metode Net Dan Gross Up Pada KAP Jimmy Andrianus Malang - Via Putri Rizkawijaya; Silvia Indrarini (Akubis : Jurnal Akuntansi dan Bisnis, 2023)
This study aims to analyze the comparison of Article 21 PPh calculations using the net and gross up methods at KAP Jimmy Andrianus. This type of case study research uses literature study and field study data collection methods, using observation, interview, and documentation data collection techniques. The problem in this study is that the company has not made tax payment calculations efficiently, because the company in tax calculations still uses the net method which is considered less effective from the company's point of view. This can be seen from the greater amount of tax paid in 2019, resulting in a greater profit before tax and an impact on the greater amount of tax paid. The results of the analysis using the gross up method show that the amount of corporate income tax is smaller, but it will result in a greater amount of expenses incurred by the company due to the increase in the amount of salary paid and the decrease in profit at the end of the year.